2016
DOI: 10.1037/xge0000232
|View full text |Cite
|
Sign up to set email alerts
|

Competing while cooperating with the same others: The consequences of conflicting demands in co-opetition.

Abstract: Numerous studies comparing the effects of competition and cooperation demonstrated that competition is detrimental on the social level. However, instead of purely competing, many social contexts require competing while cooperating with the same social target. The current work examined the consequences of such "co-opetition" situations between individuals. Because having to compete and to cooperate with the same social target constitutes conflicting demands, co-opetition should lead to more flexibility, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 93 publications
0
49
0
2
Order By: Relevance
“…Throughout most of life, goal interdependence is not positive, negative, or null but a collection of dependencies of all three types arranged in a dynamic goal hierarchy. Previous researchers define interpersonal coopetition as “a situation in which two individuals or parties need to invest effort into a joint task (i.e., cooperation) while ultimately the success of one is detrimental to the success of the other (i.e., competition)” (Landkammer & Sassenberg, , p. 1671). Tsai () investigated intergroup coopetition and found that knowledge sharing increased as result of cooperation between groups who interacted informally but decreased as a result of competition between groups within the formal organizational hierarchy.…”
Section: Future Researchmentioning
confidence: 99%
“…Throughout most of life, goal interdependence is not positive, negative, or null but a collection of dependencies of all three types arranged in a dynamic goal hierarchy. Previous researchers define interpersonal coopetition as “a situation in which two individuals or parties need to invest effort into a joint task (i.e., cooperation) while ultimately the success of one is detrimental to the success of the other (i.e., competition)” (Landkammer & Sassenberg, , p. 1671). Tsai () investigated intergroup coopetition and found that knowledge sharing increased as result of cooperation between groups who interacted informally but decreased as a result of competition between groups within the formal organizational hierarchy.…”
Section: Future Researchmentioning
confidence: 99%
“…Better performance on the RAT was also shown following the activation of the counterfactual (mental simulation) mindset—the simultaneous accessibility of both the actual outcome and the possibility of a converse counterfactual outcome (Galinsky & Moskowitz, ; Galinsky, Moskowitz, & Skurnik, ; Kray, Galinsky, & Wong, ). Using another measure of creativity—the generation of different ideas—Landkammer and Sassenberg () have found that priming participants with both cooperation and competition goals (which they termed “co‐opetition”) led to the generation of more differentiated ideas compared to priming participants with a single goal.…”
Section: The Conflict Mindset Expands Cognitive Scopementioning
confidence: 99%
“…"Co-opetition" mindset (Landkammer & Sassenberg, 2016) Participants are primed with both cooperation and competition goals.…”
Section: Remote Associations Test (Rat)mentioning
confidence: 99%
“…Landkammer and Sassenberg (2016) argued that experiencing co-opetition activates mixed demands ("cooperate and compete") that are often considered contradictory. As a consequence, schematic competitive thinking cannot be applied and, thus, cannot guide behavior.…”
Section: Thinkingcompetitivelycooperativelyorboth:therole Ofcognitimentioning
confidence: 99%